VALIDATION OF TECHNOLOGY COMPONENTS FOR PEANUT POD BORER (Etiella zinckenellaTriet.) CONTROL - Prayogo, Yusmani; Santi Yudha Ika Bayu, Marida (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Peanut pod borer caused by Etiella zinckenella is one of the important pests of peanut in Indonesia. The symptoms of E. zinckenella attack are blackened pods and rotten seeds, causing yield loss up to 90%. The research aim was to validate the efficacy of various control technology components of peanut pod borer pests. The research was conducted at the Natar (Lampung) experimental station from April to August 2014. The research was arranged using a complete randomized design (CRD) method, the treatment consisted of six control technology components, and treatment was repeated four times. The results showed that the more larvae found in the pods, the greater the damage of the pods are crushed by larvae. Application of lambda cyhalothrin insecticide (P6) starting at 35–70 days after planting (DAP) was not able to suppress larval populations of E. zinckenella so that damaged pods were also larger and not significantly different from without control (P0). Lamda sihalotrin insecticide application also harms the survival of natural enemies (predators and parasitoids). Lamda cyhalothrin insecticides can be combined with other control components such as soybean trap plants, thiametoxam and carbofuran and parasitoid of Trichogramma bactrae-bactrae to control of peanut pod borer. Application of Lecanicillium lecanii biopesticide was combined with chemical insecticides thiametoxam or carbofuran can suppress E. zinckenella larvae and yield loses, beside it can safety against the survival of predators the order Araneida and Coleoptera and parasitoid of Hymenoptera and Diptera. Biopesticides of L. lecanii were combined with tiametoxam or carbofuran insecticides can be recommended for control agents of peanut pod borer E. zinckenella.